Retinoic acid modulation of granule cell activity and spatial discrimination in the adult hippocampus - Yeo, Yun-Gwon; Park, Jeongrak; Kim, Yoonsub; Rah, Jong-Cheol; Shin, Chang-Hoon; Oh, Seo-Jin; Jang, Jin-Hyeok; Lee, Yaebin; Yoon, Jong Hyuk; Oh, Yong-Seok (Frontiers in Cellular Neuroscience, 2024)
Retinoic acid (RA), derived from vitamin A (retinol), plays a crucial role in modulating neuroplasticity within the adult brain. Perturbations in RA signaling have been associated with memory impairments, underscoring the necessity to elucidate RA's influence on neuronal activity, particularly within the hippocampus. In this study, we investigated the cell type and sub-regional distribution of RA-responsive granule cells (GCs) in the mouse hippocampus and delineated their properties. We discovered that RA-responsive GCs tend to exhibit a muted response to environmental novelty, typically remaining inactive. Interestingly, chronic dietary depletion of RA leads to an abnormal increase in GC activation evoked by a novel environment, an effect that is replicated by the localized application of an RA receptor beta (RARβ) antagonist. Furthermore, our study shows that prolonged RA deficiency impairs spatial discrimination-a cognitive function reliant on the hippocampus-with such impairments being reversible with RA replenishment. In summary, our findings significantly contribute to a better understanding of RA's role in regulating adult hippocampal neuroplasticity and cognitive functions.